SOME POSSIBLE IMPACTS OF CLIMATE CHANGE ON HUMAN SECURITY IN THAILAND - Vesteri, Ulla-Maria Liisa; Nontasak, Tatree (PEOPLE: International Journal of Social Sciences, 2018)
Climate change impacts such as sea-level rise, droughts and floods can pose a threat to human security in Thailand. This research is asking what kinds of challenges does climate change pose to Thailand and how will those challenges effect human security. Climate change is well researched topic but previous work has failed to address it through the lens of human security. This research wants to underline that climate change is not only an environmental problem, but can effect societies in larger scale. The methodology used in this research involved documentary research supplemented by three expert interviews. The findings of this research confirm that climate change impacts can effect human security of Thai population by destroying the crops, real estate and infrastructure. Therefore, it is recommended for Thailand to spread awareness of environmental issues, continue regional co-operation with ASEAN, and invest in research in order to enhance mitigation and adaptation measures. Thailand should also prepare for climate related migration in the future.